In the house of wilderness : a novel - White, Charles Dodd, 1976- (Swallow Press, an imprint of Ohio University Press, 2018)
After months of wandering homeless through the landscape of Appalachia, a young woman named Rain finds herself part of a desperate family driven by exploitation and abuse. A harrowing story of choice and sacrifice, In the House of Wilderness is a novel about the modern South and how we fight through hardship and grief to find a way home.